2014
DOI: 10.3109/09638288.2014.892641
|View full text |Cite
|
Sign up to set email alerts
|

Religious faith and self-efficacy among stroke patients in Kuwait: health professionals’ views

Abstract: It is known that patients' self-efficacy in rehabilitation can be strengthened through a number of strategies such as goal-setting and feedback. This study suggests that for Muslim patients in Kuwait, health professionals also need to be mindful of their need for religious empowerment. Implications for Rehabilitation Muslim religious beliefs may influence self-efficacy in stroke patients in the Kuwaiti context. Patients who regard themselves as working in partnership with their God may feel empowered and more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
1
5
0
3
Order By: Relevance
“…These thoughts were attributed to the anticipation of an inability to cope with physical disabilities, pain, and depression. In congruence to this finding, studies found that stroke, depression, and pain increased the risk for suicidal ideation and attempts, independent of other factors that are known to be associated with suicidality, suggesting that stroke per se may be an independent risk factor for suicidality (38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Demographic Characteristicsmentioning
confidence: 86%
“…These thoughts were attributed to the anticipation of an inability to cope with physical disabilities, pain, and depression. In congruence to this finding, studies found that stroke, depression, and pain increased the risk for suicidal ideation and attempts, independent of other factors that are known to be associated with suicidality, suggesting that stroke per se may be an independent risk factor for suicidality (38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Demographic Characteristicsmentioning
confidence: 86%
“…The view of spiritual and religious beliefs in coping with life after stroke may not always fit into the health professionals’ view, which can sometimes be based on assessments and ability to function in a set way. There is some research to support health professionals’ views on inclusion of religion into stroke rehabilitation with Muslim stroke patients and that health professionals could support religious patients to enhance self‐efficacy in stroke rehabilitation (Omu & Reynolds ). The evidence base for the inclusion of religion in rehabilitation of stroke, however, is very small.…”
Section: Discussionmentioning
confidence: 99%
“…According to Bandura (1977) [ 6 ], efficacy expectation is the contentment that one can successfully carry out a behavior required to produce the outcomes. Although not measured here, religious beliefs could influence the individuals’ acceptance of the disease and its effects, perceiving it as part of their fate predestined by God [ 22 ].…”
Section: Discussionmentioning
confidence: 99%